Diseño del sistema de recolección de residuos sólidos urbanos para el barrio La Argentina de la Parroquia Guamaní al Sur de Quito - Paspuel Hernández, Fausto Vicente (2010)
Finally, we propose solution built for micro territorial space with possibilities of adapting to others with similar characteristics, to determine the methodological procedure to change driving habits of solid waste end urabanos and operational logic systems of collection, treatment and disposal